Characterization of acetate transport in colorectal cancer cells and potential therapeutic implications - Ferro, Suellen (2016)
Acetate, together with other short chain fatty acids has been implicated in colorectal cancer (CRC) prevention/therapy. Acetate was shown to induce apoptosis in CRC cells. The precise mechanism underlying acetate transport across CRC cells membrane, that may be implicated in its selectivity towards CRC cells, is not fully understood and was addressed here. We also assessed the effect of acetate in CRC glycolytic metabolism and explored its use in combination with the glycolytic inhibitor 3-bromopyruvate (3BP). We provide evidence that acetate enters CRC cells by the secondary active transporters MCT1 and/or MCT2 and SMCT1 as well as by facilitated diffusion via aquaporins. CRC cell exposure to acetate upregulates the expression of MCT1, MCT4 and CD147, while promoting MCT1 plasma membrane localization. We also observed that acetate increases CRC cell glycolytic phenotype and that acetate-induced apoptosis and anti-proliferative effect was potentiated by 3BP. Our data suggest that acetate selectivity towards CRC cells might be explained by the fact that aquaporins and MCTs are found overexpressed in CRC clinical cases. Our work highlights the importance that acetate transport regulation has in the use of drugs such as 3BP as a new therapeutic strategy for CRC.